QUESTION TYPES, MODIFICATIONS AND UNDRLYING REASONS AND IMPLICATIONS FOR STUDENT ORAL PRODUCTION - Wihadi, Marwito (2010)
Considering the values of teacher questioning in language learning. this research investigates the real practices of teacher questions in the speaking class at a private university in Bandung. The present study aimes (1) to find question types that the teacher employs in teacher-student interactions, (2) to find the teacher's question modification techniques when communication breakdowns occur, (3) to find out the effects of teacher-posed questions on students' oral production, (4) to find out the reason(s) why the teacher employs a particular question type the most frequently. A teacher is involved as a research participant, teaching 20 freshmen majoring in English Department at a Language Faculty. Two sessions are attended and video-taped by the researcher whose role is as a non-participant observer. Data are obtained from observations and a guided interview. All data are analyzed and described qualitatively and quantitatively to answer the research questions. The study reveals that echoic and epistemic questions prevail in the speaking class, notifying, in particular, close referential questions are predominant, while echoic questions are rare. In addition, pauses are a dominant question modification technique employed much more frequently than other five ones. Meanwhile, a code-switching technique is not existent. It is, subsequently, found that referential or divergent questions affect the students to produce the most utterances. Eventually, the teacher's underlying motives to pose referential questions the most frequently are learning involvement, learners' language proficiency, and contextual learning. These findings are expected to contribute to better insights of teacher questioning practices in the classroom and valuable inputs for teacher training programs. Furthermore, this study recommends that the subject teacher should be both more productive in diversity of posed question types and employed modification question techniques. Also, more allocated wait-time following question poses should be well facilitated.